Proposal to introduce disaster risk management topics in master programs in ESAN Graduate School of Business - Dejo Esteves, Cecilia (2016)
This paper aims to explain and present a proposal to introduce Disaster Risk Management (DRM) topics into ESAN Graduate School of Business Master’s programs. Although disasters have cost Peru more than USD 7,600 million in the past 2 decades the business sector, particularly Small and Medium Enterprises, have not developed preventive or continuity plans mainly because they are not familiar with DRM topics. Taking this into consideration, the paper presents a detailed academic/curricular proposal for DRM topics such as business continuity, business ethics, corporate social responsibility, and sustainable management. Additionally, it introduces the idea of promoting Disaster Risk Management (DRM) topics to the Peruvian business community as a strategy to enhance the graduate education.